Fish Migration River Monitoring Plan - Calles, Olle; Griffioen, Ben; Winter, Erwin; Watz, Johan; Nyqvist, Daniel; Hagelin, Anna; Gustafsson, Stina; Österling, Martin; Piccolo, John; Greenberg, Larry; Bergman, Eva (Karlstads universitet, Institutionen för miljö- och livsvetenskaper, 2014)
Fish have problems passing the Afsluitdijk Dam that separates the Wadden Sea from Lake IJsselmeer. To re-establish the connectivity and thereby allow fish to pass there is an initiative to build a fishway, the Fish Migration River (FMR), at the Konwerderzand sluice complex. This report proposes a monitoring program to evaluate the functionality of the FMR, but also to monitor passage possibilities through the existing sluices. The goals of the monitoring plan are to estimate 1) The overall passage past the Afsluitdijk dam to and from Lake IJsselmeer, 2) The attraction efficiency, 3) The passage efficiency, and 4) The use of the FMR as habitat and for acclimatization for the transition into freshwater. We present an overview of previous and ongoing monitoring in the area to establish the current state of knowledge. The report also includes a presentation of available and suitable methods for a future monitoring program considering the broad spectra of target fish species, and their abundances. The proposed program includes a description of study design and available techniques and cost-estimates of the monitoring program. The proposed program will target ten species: European eel (aal), flounder (bot), three-spined stickleback (dreidoornige stekelbaars), twait shad (fint), North Sea houting (houting), river lamprey (rieverprik), smelt (spiering), Atlantic salmon (zalm), brown trout (forel) and sea lamprey (zeeprik). The monitoring program includes plans for how to capture, tag and track the study fish using the most suitable tagging techniques. Furthermore, the most optimal sites for installation of automatic data detection stations are identified. The total cost for the proposed project is 3.5 M€ and covers both investments in equipment and costs for personnel. However, if costs for investments in techniques such as RFId-stations and fish counters are excluded, the total cost is reduced to 1 M€ for a program running two years before and four years after the completion of the FMR. The program is considered ...